Patients perceived challenges in seeking dental care in Komfo Anokye Teaching Hospital - Kwame Adu Okyere Boadu; Richard Okyere Boadu; Esther Priscilla Biamah Danquah; Nana Atuahene Oti; John Billy Owusu Quarshie; Nana Bempong Owusu-Ankomah; Moses Yeboah Addo (PLoS ONE, 2025)
Background Access to dental care services remains a global challenge, with millions encountering barriers that hinder their utilization, despite the recognized importance of oral health to overall well-being. The intricate relationship between oral health and general well-being highlights the severe impact of oral disorders on global economies and public health systems when access barriers exist. This study aimed to assess the perceived challenges in seeking dental care among patients at the Oral Health Directorate of Komfo Anokye Teaching Hospital. Methods This study employed a mixed methods approach, combining both quantitative and qualitative research methods for 130 respondents. With the quantitative approach: it was a cross-sectional design where structured questionnaires were administered to participants and data was analyzed using SPSS IBM version 23. The qualitative approach on the other hand, utilized semi-structured interviews to explore participants’ experiences, perspectives, and challenges related to accessing dental care. Data was analyzed using thematic analysis to identify key themes and patterns within the responses. The study had a response rate of 94.89%. Results Most respondents were females (56.2%) and aged 25–34 (26.9%). Approximately 55.4% had encountered barriers, with cost and lack of appointment times being major concerns. Regarding challenges at the dental clinics, lengthy waits (63.2%) and dental anxiety (77.0%) were the most common concerns. Gender and marital status were the only demographic characteristics which were statistically significantly associated with quality of care sought. Gender had a p-value of 0.00, indicating strong evidence of an association, while marital status had a p-value of 0.055, suggesting moderate evidence of an association. Marital status and education were found to be statistically significantly associated with perceived treatment-seeking behaviours, with p-values of 0.012 and 0.009 respectively. Postponement of dental care results in deteriorating oral health, higher expenses, and emotional strain for patients. The study identified long wait times, unclear communication, and financial barriers as key challenges. Patients proposed solutions including streamlined appointments, jargon-free explanations, and more affordable care options to improve dental experiences and accessibility. Conclusions Over half of respondents faced obstacles like cost and limited appointment availability. Patients also encountered challenges during dental visits, such as anxiety and long wait times. Demographics like gender, marital status, and education were linked to treatment-seeking behavior, suggesting potential disparities in access and utilization. Overall, the study highlights the complex interplay between socio-demographic factors, perceived barriers, patient experiences, and suggestions for enhancing dental care accessibility and quality.